Volume management in SAN environment - Chang-Soo Kim; Gyoung-Bae Kim; Bum-Joo Shin (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Logical volume managers have long been key components of a storage system. Their key features are creation of logical or virtual views of physical storage devices and support for various software RAID levels. These make it possible to overcome the limits to capacity, availability and performance of a physical storage device. Most logical volume managers are operated in a single system environment. They are not adequate for SAN (storage area network) environments where several hosts share and access a logical volume at the same time. Some recent logical volume managers are run in a multi-host environment. However, they cannot support the enterprise computing environments in which the system must support 24/spl times/7/spl times/365 uptime operations such as online resizing and online backup. We propose a logical volume manager called 'SANtopia Volume Manager' that supports multihost environments and provides various volume management features to support enterprise computing. Also it is a cluster enabled logical volume manager that maximizes the parallelism for high performance, and provides high scalability and high availability.